112 Safety and biochemical efficacy of sodium–glucose cotransporter 2 inhibitors based on cardiovascular risk profile and volume status in a real-world diabetic population. (8th December 2021) - Gitto, Mauro; Kotinas, Alexios; Terzi, Riccardo; Oliva, Angelo; Zagoreo, Jorgele; Reimers, Bernhard; Stefanini, Giulio G; Mirani, Marco; Favacchio, Giuseppe; Condorelli, Gianluigi; Panico, Cristina
Abstract: Aims: Sodium–glucose cotransporter 2 inhibitors (SGLT2i) have become a first-line cardiovascular medication. However, their potential side effects still limit a widespread use in real-world clinical practice. Further, there is uncertainty about the mechanisms mediating SGLT2i-associated cardiovascular benefit. Methods: We performed a retrospective analysis on consecutive diabetic patients who were prescribed a SGLT2i in a tertiary referral centre. Patients who completed at least 1 year of treatment were included in the data analysis. Changes in glycated haemoglobin, weight and haematocrit were evaluated and compared across two cardiovascular risk categories, defined through the inclusion criteria of three large randomized clinical trials. Additionally, a modified clinical score (mH2 FPEF) was applied to detect the probability of heart failure with preserved ejection fraction (HFpEF). Results: Of the 459 patients screened from 2015 to 2020, 312 completed 1 year of treatment (68.0%), 92 interrupted the treatment prematurely (20.0%) and 55 were lost to follow-up (12.0%). The most common causes of drug discontinuation were genital or urinary tract infections (9.4%) and poor glycaemic control (5%). At 1 year, a significant reduction in glycated haemoglobin concentration (−0.6 ± 1.4%, P  < 0.001) and body weight (2.4 ± 4.6 Kg, P  < 0.001) was observed and was comparable between patients at high vs. low cardiovascular risk. Haematocrit increase at 1 year (2.3 ± 3.3%, P  < 0.001) was more marked in patients with high cardiovascular risk and low baseline haematocrit. Among patients with no established heart failure ( N  = 295), 156 (52.9%) had >50% probability of HFpEF (mH2 FPEF ≥3). Conclusions: In a real-world population of diabetic patients, SGLT2i were well-tolerated at 1 year and led to improved glycaemic control and weight loss. Haematocrit increase was more consistent in patients with high cardiovascular risk and signs of fluid overload, indicating the potentially beneficial role of euvolemic restoration. More than half of these diabetic patients had a high likelihood of unrecognized HFpEF.